Officer Buckle and Gloria - Rathman, Peggy (New York : Scholastic Inc, 1995)
No one pays attention to Officer Buckle when he's giving out safety tips, until Gloria, his police dog, surprises them!
This book won the 1996 Caldecott Medal
Keywords: Police--Fiction; Dogs--Fiction; Safety--Fiction